Variants of Tax Planning Method Based on Tax Consultant’s Perpective - Mandasari, Jayanti; Khairin, Fibriyani Nur (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2024)
The purpose of this research is to reveal the metode best practice of the tax consultant's side regarding corporate tax planning. The method used in this research is qualitative with a case study approach. This method is considered suitable because it helps researchers to reveal in dept nh the practice of tax planning. The results of the study reveal that the best practices most often used by tax consultants are three, namely depreciation in terms of differences between accounting and tax regarding the useful life and methods used. inventory by choosing between First In First Out and average, both of these methods have their respective advantages and disadvantages, making differences of opinion between senior and junior tax consultants, the last practice most often used is cost shifting. These three practices are proven to be able to minimize the tax burden, but of course there must be considerations made by tax consultants in choosing the best practice to do. The findings of this study can be useful for taxpayers in terms of education and learning related to tax planning, besides that for future researchers it is recommended not only to focus on practices but also to lead to their meaning.